Braking torque distribution for hybrid electric vehicles based on nonlinear disturbance observer. (November 2019) - Zhao, Xiuchun; Guo, Ge
This article develops a two-layer brake control framework for hybrid electric vehicles equipped with both hydraulic and regenerative braking systems. In order to obtain better braking performance and higher regenerative braking efficiency, a cooperative braking control strategy is presented. In the first layer, a simple but robust brake controller is proposed to overcome the uncertainties of road condition and load variation by introducing a nonlinear disturbance observer. The convergence and stability are proved through the Lyapunov theory. In the second layer, a novel braking torque distribution strategy is proposed based on battery state of charge, which can recover more braking energy and improve the health of the battery. By simulation, the braking strategy is proved to be effective under various conditions and it shows a good compromise between the battery state of charge health and the regenerated energy recovery.